APPLICATION OF FERTILIZATION TIME AND NITROGEN DOSAGE ON PEANUT PLANT (Arachis hypogaea L.) - Anak Agung Sagung Putri Risa Andriani; I Nengah Suaria; I Wayan Yudiana; Yohanes Parlindungan Situmeang; Anak Agung Ngurah Mayun Wirajaya; I Gusti Bagus Udayana (SEAS (Sustainable Environment Agricultural Science), 2017)
Abstract This study aims to determine the effect of treatment of fertilization time and dosage of nitrogen to the growth and yield of peanut plants. This experiment is a two-factor experiment with incomplete randomized block design. The first factor is the time (S) of fertilizer consisting of three levels: During planting (S0), 15 days after planting (S1), 30 days after planting (S2), The second factor is the dosage of Nitrogen (N) fertilizer consisting of three levels: 25 kg/ha (N1), 50 kg/ha (N2). The results showed that treatment of fertilization time and a dose of nitrogen showed no significant effect on plant height, maximum leaf number, leaf area index, the total pod containing, total void pod, total pod number, oven dry weight of oven plants, and harvesting index. The interaction of nitrogen dose with a time of fertilization gave a very real effect to most observed variables except for maximum plant height, maximum leaf number, leaf area, harvest index that is not significant. The high dry weight of seed oven per plant was obtained at the fertilizer interaction treatment at 15 days after planting and the dose of nitrogen 25 kg/ha was 30.33 g and or increased by 152.75% and when compared with the control of 12.00 g. From a result of regression analysis got an optimum dose of nitrogen fertilizer that is 34.15 kg/ha with the dry weight of oven seeds per plant maximum 26.73 g. Keywords: Fertilization time, nitrogen dosage, peanut result